A COMPARATIVE ANALYSIS OF CYBORG REBELLION IN EEKHOUT’S COG AND PULLMAN’S THE GOLDEN COMPASS - J., Sripadmadevi; Yvette, Liliane Maria (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Cyborgs, a relatively groundbreaking aspect of Donna Haraway’s manifesto, is carefully termed to denote modern civilisation as a whole. The upholding of militarism and patriarchal capitalism parallelly undermining and marginalising of novel diversity is of debate in Haraway’s Manifesto. Eekhout’s Cog and Pullman’s The Golden Compass testify to Haraway’s idea of Cyborg in a collective and distinguishing way. Derived from Science Fiction, Cyborgs tend to be viewed as creatures of Dystopian value. Haraway, on the other hand, wittily phrases the word denoting each and every civilian of the present day. The novels Cog and The Golden Compass, portray Haraway’s concept of illegitimate offspring being exceedingly unfaithful to their origin. According to this idea, Cyborgs, have the tendency to rebel, in order to find utopian values in a dystopian forefront. The present paper deals with the concept of Cyborg as the new human and attempts a comparative analysis of Cyborg instituted rebellion through the eyes of Cog and Lyra the protagonists of Cog and The Golden Compass respectively.